Sexual behaviour patterns and STI risk: results of a cluster analysis among men who have sex with men in Portugal - Martina Furegato (BMJ Publishing Group, 2021)
Objectives Portugal has the highest HIV incidence rate in Western Europe. The proportion assigned to sexual contact between men recently increased to more than 30% of all HIV infections. Men who have sex with men (MSM) are vulnerable to the acquisition of other sexually transmitted infections (STIs), increasing the per-contact risk of HIV infection. Building on syndemic theory, the aim of this analysis was to identify patterns of current sexual behaviour in MSM, and explore their relationship with self-reported current, past STI diagnoses and HIV positive serostatus.Design A cross-sectional behavioural survey was conducted in Portugal among MSM, using a community-based participatory research approach. Hierarchical cluster analysis was used to identify patterns including behavioural and demographic factors.Results The analysis resulted in six clusters. Three clusters showed higher rates of current STI diagnosis (ranging from 11.7% to 17.1%), past STI diagnosis (ranging from 25.5% to 41.5%) and HIV positive serostatus (ranging from 13.0% to 16.7%). From the three clusters scoring lower on current and past STI and HIV diagnoses, one was characterised by a high number of sexual partners (62% had more than 12 partners in the last year), a high proportion (94.6%) of frequent visits to gay venues to meet sexual partners and high alcohol use (46.1%). The other two clusters scored lower on high risk sexual behaviour.Conclusion Factors other than sexual behaviour appear to reinforce the vulnerability to STIs and HIV of some MSM in this study, suggesting a syndemic of STIs, HIV and other adverse conditions. More research is needed to better understand the drivers of the STI/HIV epidemic in Portuguese MSM, using a concept that goes beyond risk behaviour, to develop effective combination prevention interventions.